2012
DOI: 10.1002/ijc.27439
|View full text |Cite
|
Sign up to set email alerts
|

Activation of lytic cycle of Epstein‐Barr virus by suberoylanilide hydroxamic acid leads to apoptosis and tumor growth suppression of nasopharyngeal carcinoma

Abstract: Nasopharyngeal carcinoma (NPC) is strongly associated with Epstein-Barr virus (EBV). We reported that suberoylanilide hydroxamic acid (SAHA) induced EBV lytic cycle in EBV-positive gastric carcinoma cells and mediated enhanced cell death. However, expression of EBV lytic proteins was thought to exert antiapoptotic effect in EBV-infected cells. Here, we examined the in vitro and in vivo effects of SAHA on EBV lytic cycle induction in NPC cells and investigated the cellular consequences. Micromolar concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
140
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(148 citation statements)
references
References 28 publications
8
140
0
Order By: Relevance
“…Our laboratory has previously shown that SAHA could significantly induce viral lytic cycle in EBV-positive gastric carcinoma and NPC cells and mediates enhanced apoptosis (11,12). The lytic cycle induction and tumor growth suppression mediated by SAHA could also be observed in NPC xenografts established in nude mice (12).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…Our laboratory has previously shown that SAHA could significantly induce viral lytic cycle in EBV-positive gastric carcinoma and NPC cells and mediates enhanced apoptosis (11,12). The lytic cycle induction and tumor growth suppression mediated by SAHA could also be observed in NPC xenografts established in nude mice (12).…”
Section: Introductionmentioning
confidence: 97%
“…Suberoylanilide hydroxamic acid (SAHA; also known as vorinostat) is a HDAC inhibitor approved by FDA for the treatment of cutaneous T-cell lymphoma. It alters gene expression by histone acetylation and mediates various cellular effects, including cell differentiation, cell-cycle arrest, and apoptosis, in different cancer cell types (9)(10)(11)(12). Combination of bortezomib and SAHA (bortezomib/SAHA) was shown to be effective in the treatment of hematologic malignant cells such as multiple myeloma (13), mantle cell lymphoma (14), cutaneous T-cell lymphoma (15), and leukemia (16,17).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…29 This pathway results in cellular differentiation or apoptosis of cancerous prostate and nasopharyngeal cells in vitro and prevents tumor growth in vivo. 14 41 as well as human immunodeficiency virus (HIV) infections 42 and in models of Huntington's disease. 43 In HIV, the virus remains latent in CD4 + T-cells; this stage is not susceptible to highly active anti-retroviral therapy (HAART) and thus patients will exhibit a rebound in viral load following cessation of treatment.…”
Section: Ebv-related Infectionsmentioning
confidence: 99%